The potential actions of angiotensin-converting enzyme II (ACE2) activator diminazene aceturate (DIZE) in various diseases - Qaradakhi, Tawar; Gadanec, Laura Kate; McSweeney, Kristen Renee; Tacey, Alexander; Apostolopoulos, Vasso; Levinger, Itamar; Rimarova, Kvetoslava; Egom, Emmanuel E; Rodrigo, Luis; Kruzliak, Peter; Kubatka, Peter; Zulli, Anthony (Clinical and experimental pharmacology & physiology, 2020)
The renin angiotensin system (RAS) regulates fluid balance, blood pressure and maintains vascular tone. The potent vasoconstrictor angiotensin II (Ang II) produced by angiotensin-converting enzyme (ACE) comprises the classical RAS. The non-classical RAS involves the conversion of Ang II via ACE2 into the vasodilator Ang (1-7) to counterbalance the effects of Ang II. Furthermore, ACE2 converts AngA into another vasodilator named alamandine. The over activation of the classical RAS (increased vasoconstriction) and depletion of the non-classical RAS (decreased vasodilation) results in vascular dysfunction. Vascular dysfunction is the leading cause of atherosclerosis and cardiovascular disease (CVD). Additionally, local RAS is expressed in various tissues and regulates cellular functions. RAS dysregulation is involved in other several diseases such as inflammation, renal dysfunction and even cancer growth. An approach in restoring vascular dysfunction and other pathological diseases is to either increase the activity of ACE2 or reduce the effect of the classical RAS by counterbalancing Ang II effects. The antitrypanosomal agent, diminazene aceturate (DIZE), is one approach in activating ACE2. DIZE has been shown to exert beneficial effects in CVD experimental models of hypertension, myocardial infarction, type 1 diabetes and atherosclerosis. Thus, this review focuses on DIZE and its effect in several tissues such as blood vessels, cardiac, renal, immune and cancer cells.
Keywords: Diminazene; aktivátory enzymů; renin-angiotensin systém; angiotensin-konvertující enzym 2; kardiovaskulární nemoci; zvířata; Enzyme Activation; lidé; Renin-Angiotensin System; Cardiovascular Diseases; Animals; Angiotensin-Converting Enzyme 2; diminazen; Enzyme Activators; Humans; Neoplasms; aktivace enzymů; nádory